Heterologous expression of the Haynaldia villosa pattern-recognition receptor CERK1-V in wheat increases resistance to three fungal diseases - Anqi Fan; Luyang Wei; Xu Zhang; Jia Liu; Li Sun; Jin Xiao; Yajia Wang; Haiyan Wang; Jian Hua; Singh, Ravi P.; Zongkuan Wang; Xiue Wang (Elsevier, 2022)
Wheat production is under continuous threat by various fungal pathogens. Identification of multiple-disease resistance genes may lead to effective disease control via the development of cultivars with broad-spectrum resistance. Plant Lysin-motif (LysM)-type pattern-recognition receptors, which elicit innate immunity by recognizing fungal pathogen associated molecular patterns such as chitin, are potential candidates for such resistance. In this study, we cloned a LysM receptor-like kinase gene, CERK1-V, from the diploid wheat relative Haynaldia villosa. CERK1-V expression was induced by chitin and Blumeria graminis f. sp. tritici, the causal agent of wheat powdery mildew. Heterologous overexpression of CERK1-V in wheat inhibited the development of three fungal pathogens, thereby increased resistance to powdery mildew, yellow rust, and Fusarium head blight. CERK1-V physically interacted with the wheat LysM protein TaCEBiPs. CERK1-V/TaCEBiPs interaction promoted chitin recognition and activated chitin signal transduction in wheat. Transgenic plants with excessively high CERK1-V expression showed high resistance but abnormal plant growth, whereas plants with moderate expression level showed adequate resistance level with no marked impairment of plant growth. In transgenic lines, RNA-seq showed that gene expression involved in plant innate immunity was activated. Expression of genes involved in photosynthesis, ER stress and multiple phytohormone pathways was also activated. Optimized expression of CERK1-V in wheat can confer disease resistance without compromising growth or defense fitness.